2020
DOI: 10.1590/1678-7757-2020-0124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lymphocyte apoptosis in patients with oral cancer

Abstract: Evaluation of lymphocyte apoptosis in patients with oral cancer Objectives: To evaluate apoptotic levels of peripheral blood mononuclear cells (PBMCs) and apoptotic regulatory proteins (Bax and Bcl-2) in lymphocyte subsets of oral cancer (OC) patients and healthy controls (HC). Methodology: The percentage of apoptotic cells and lymphocyte counts were measured in the first cohort using PBMCs obtained from 23 OC patients and 6 HC. In the second cohort, (OC, 33; HC, 13), the mean fluorescence intensity (MFI) of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
6
0
1
Order By: Relevance
“…They also found a high level of (Bax) Bcl-2 associated X, a pro-apoptotic protein, and B-cell lymphoma-2 (Bcl-2), an anti-apoptotic protein ratio, in oral cancer stage IV patients. Tumor size, lymph node involvement, and the Bax/Bcl-2 ratio were also higher in advance-stage tumors, which suggested that Bax/Bcl-2 ratio levels are associated with OSCC aggressiveness [92]. In our study also, we observed that 43 (68%) of the OSCC patients had peripheral lymphocyte levels <1.980, though not statistically significant, which suggests a poor prognosis in these patients, and the majority of our patients had advanced tumors.…”
Section: Discussionsupporting
confidence: 46%
“…They also found a high level of (Bax) Bcl-2 associated X, a pro-apoptotic protein, and B-cell lymphoma-2 (Bcl-2), an anti-apoptotic protein ratio, in oral cancer stage IV patients. Tumor size, lymph node involvement, and the Bax/Bcl-2 ratio were also higher in advance-stage tumors, which suggested that Bax/Bcl-2 ratio levels are associated with OSCC aggressiveness [92]. In our study also, we observed that 43 (68%) of the OSCC patients had peripheral lymphocyte levels <1.980, though not statistically significant, which suggests a poor prognosis in these patients, and the majority of our patients had advanced tumors.…”
Section: Discussionsupporting
confidence: 46%
“… 31 Bcl-2 and Bax are important factors affecting the survival and proliferation of NK cells, as well as other lymphocytes. 32 , 33 In order to understand the proliferation-related signaling pathway, we detected the expression of Bcl-2 and Bax both in mRNA and protein levels in NK cells induced by apigenin, and the Bcl-2 to Bax ratio was analyzed in this study. The results of qRT-PCR and Western blotting analysis showed that apigenin could inhibit gene and protein expression of Bax in NK cells after 72 h induction, especially in 5 μM and 10 μM dose groups.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the idea that chrysin primarily affects tumor growth by inducing apoptosis via death receptors and/or activating proapoptotic members of the B cell lymphoma 2 (Bcl-2) pathway. 27,28 The limitations of the study were that all experiments were conducted in vitro and on only two cell lines (HSC4 and SCC25). To determine the clinical efficacy of chrysin on OSCC cells, additional in vitro and in vivo studies on additional OSCC cell lines are required.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the idea that chrysin primarily affects tumor growth by inducing apoptosis via death receptors and/or activating proapoptotic members of the B cell lymphoma 2 (Bcl-2) pathway. 27 28 …”
Section: Discussionmentioning
confidence: 99%